Speeding up access to new drugs for CF: Considerations for clinical trial design and delivery - Davies, Jane C; Drevinek, Pavel; Elborn, J Stuart; Kerem, Eitan; Lee, Tim; Amaral, Margarida D; de Boeck, Kris; Davies, Jane C; Drevinek, Pavel; Elborn, J Stuart; Kerem, Eitan; Lee, Tim (Journal of cystic fibrosis, 2019)
The last decade has witnessed developments in the CF drug pipeline which are both exciting and unprecedented, bringing with them previously unconsidered challenges. The Task Force group was brought together to consider these challenges and possible strategies to address them. Over the last 18 months, we have discussed internally and gathered views from a broad range of individuals representing patient organisations, clinical and research teams, the pharmaceutical industry and regulatory agencies. In this and the accompanying article, we discuss two main areas of focus: i) optimising trial design and delivery for speed and efficiency; ii) drug development for patients with rare CFTR mutations. We propose some strategies to tackle the challenges ahead and highlight areas where further thought is needed. We see this as the start of a process rather than the end and hope herewith to engage the wider community in seeking solutions to improved treatments for all patients with CF.
Keywords: Drug Development; Quality Improvement; Humans; Mutation; vyvíjení léků; Cystic Fibrosis; Clinical Trials as Topic; protein CFTR; klinické zkoušky jako téma; Membrane Transport Modulators; modulátory membránového transportu; zlepšení kvality; cystická fibróza; výzkumný projekt; lidé; objevování léků; Drug Discovery; mutace; Research Design; Cystic Fibrosis Transmembrane Conductance Regulator